Komunikasi Simbolik dalam Konten Instagram @Elizabethangelalorenza sebagai Upaya Rebranding Diri Menjadi Lady Bikers - Adrianty, Rizky Amelia; Meliala, Robbikal Muntaha; Bender, George Wilhelm (Innovative: Journal Of Social Science Research, 2025)
The advancement of social media in the current era of globalization is growing so rapidly. This has an impact on the increasing use of social media, especially Instagram. Instagram is ranked 2nd out of 10 social media with the most users in Indonesia. Instagram has given birth to new influencers who are currently still trusted by several brands to promote their products or companies. In this case, this study discusses how symbolic communication in the Instagram content of @elizabethangelalorenza as an effort to rebrand herself into a lady biker and how to evaluate the effort to rebrand herself @elizabethangelalorenza into a lady biker in Indonesia. This study uses a descriptive qualitative research method through observation and in-depth interviews with related parties. The data collected is then analyzed descriptively to produce a work. Angela Lorenza's rebranding effort to become a lady biker on her Instagram has succeeded in gaining sympathy and empathy from her followers. This is proven by the suitability of positive affirmations at the mind, self, society and looking glasses levels (in accordance with George Herbert Mead's Chicago Symbolic Interactionism Theory) in Angela when interacting with her followers. Angela's rebranding efforts according to Muzzelec's theory are also applied to the renaming, repositioning, redesigning, and relaunching of Angela's content uploads on Instagram with her motorbike, her feminine masculine style of dress, and the association of her followers who now recognize Angela as a lady biker.